Spatial and Temporal Variations in Traffic-related Particulate Matter at New York City High Schools - Patel, Molini M. (2009)
Relatively little is known about exposures to traffic-related particulate matter at schools located in dense urban areas. The purpose of this study was to examine the influences of diesel traffic proximity and intensity on ambient concentrations of fine particulate matter (PM(2.5)) and black carbon (BC), an indicator of diesel exhaust particles, at New York City (NYC) high schools. Outdoor PM(2.5) and BC were monitored continuously for 4–6 weeks at each of 3 NYC schools and 1 suburban school located 20 kilometers upwind of the city. Traffic count data were obtained using an automated traffic counter or video camera. BC concentrations were 2–3 fold higher at urban schools compared with the suburban school, and among the 3 urban schools, BC concentrations were higher at schools located adjacent to highways. PM(2.5) concentrations were significantly higher at urban schools than at the suburban school, but concentrations did not vary significantly among urban schools. Both hourly average counts of trucks and buses and meteorological factors such as wind direction, wind speed, and humidity were significantly associated with hourly average ambient BC and PM(2.5) concentrations in multivariate regression models. An increase of 443 trucks/buses per hour was associated with a 0.62 μg/m(3) increase in hourly average BC at a NYC school located adjacent to a major interstate highway. Car traffic counts were not associated with BC. The results suggest that local diesel vehicle traffic may be important sources of airborne fine particles in dense urban areas and consequently may contribute to local variations in PM(2.5) concentrations. In urban areas with higher levels of diesel traffic, local, neighborhood-scale monitoring of pollutants such as BC, which compared to PM(2.5), is a more specific indicator of diesel exhaust particles, may more accurately represent population exposures.